Genre Strategy of Modern Russian-Language Poetry in Kazakhstan - Khaybullina, Angelina Airatovna; Nagumanova, Elvira Firdavilevna; Nurgali, Kadisha Rustembekovna (International Journal of Criminology and Sociology, 2022)
At the end of the 20th century, the poetry of Kazakhstan made a great stride forward, which can be compared with the ideas of the cultural revolution. Unlike Russian poetry being changed throughout the 20th century, Kazakh poetry has made a breakthrough in its development only for the last two decades, allowing it to fit the conventions of modern world poetry. The present article aims at revealing the features of the functioning of the Russian-language poetry of Kazakhstan at the end of the 20th – the beginning of the 21st century. The authors of the article define those changes that have occurred in the genre strategy of modern poetry in Kazakhstan. The genre canon is generally accepted as one of the essential manifestations of the dialogue between different texts, being a kind of recognizable quote; simultaneously, it is deformed in the works by poets of the beginning of the 21st century. The transformation of genre traditions and canons engenders a unique phenomenon in modern poetry of Kazakhstan – "the poetry of philosophers." The poets such as Sergei Kolchigin, Indira Zaripova, Zhanat Baimukhametov tend to be attributed to this category. Also, modern Russian-language poetry is distinguished by the aspiration for collecting incredibly lyrical emotion and the same "extreme" interest in extra-literary events within the boundaries of one text. All these features bespeak the formation of another poetics in modern literature of Kazakhstan.